PERSEPSI PETANI TERHADAP TEKNOLOGI SISTEM TANAM JAJAR LEGOWO PADI SAWAH (Oryza sativa L) DI DESA TAMANMARTANI KECAMATAN KALASAN KABUPATEN SLEMAN - Wahjuni, Wahjuni (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
Tamanmartani is a government program that is the integrated crop planting movement (GP-PTT) program in the year 2015. One of the components is rice planting with Legowo and planting system. But farmers until now still apply loor tile system. That the impact on the average productivity in Tamanmartani Village 5 last year only reached 5 ton/ha, from the year 2014-2018. This study was conducted from January to July 2019, in Tamanmartani Village, Kalasan District, Sleman Regency. The method used is descriptive, data collection using interviews, questionnaires, and observations using a Likert scale with precise, less precise, and incorrect categories. Respondents were determined by Proportionate Random Sampling as many as 39 farmers who participated in the program (GP-PTT). Results showed that the analysis of the perception of farmers from 4 variables on knowledge, interests, attitudes, and needs, turns out the lowest variable with a percentage of 67.09 that is the attitude variable, with the lower statement The Implementation of Tajarwo System with a percentage of 58.97%. This means that the attitude of farmers has a negative effect on farmers perception of technology in the Legowo farming system.